Oral delivery of dihydroartemisinin for the treatment of melanoma via bovine milk exosomes - Kumar D.N.; Chaudhuri A.; Dehari D.; Gamper A.M.; Kumar D.; Agrawal A.K. (My University, 2025)
Cancer, particularly skin cancer, is a major cause of mortality worldwide, with melanoma being one of the most aggressive and challenging to treat types. Current therapeutic options, such as dacarbazine (DTIC), have limitations due to dose-related toxicities like liver toxicity. Therefore, there is a need for new and effective treatments for melanoma. Dihydroartemisinin (DHA), derived from artemisinin compounds known for their anti-malarial properties, has shown promise as an anti-cancer agent. However, the clinical use of DHA faces challenges such as low solubility and toxicity, which limit its therapeutic efficacy. To overcome these challenges, we developed an exosomal formulation of DHA to enhance its anti-cancer activity and reduce metastasis. Exosomes, biological vesicles, contain many biological macromolecules such as DNA, RNAs, and many other proteins, involved in intercellular communication, were isolated and loaded with DHA using the sonication method. The loaded exosomes were characterized for size (90–103 nm), polydispersity index (PDI: 0.119–0.123), and zeta potential (-23 to -28 mV). In vitro studies demonstrated the efficacy of DHA-loaded exosomes through cytotoxicity and apoptosis assays. The molecular mechanism of action was further elucidated using immunoblotting analysis, focusing on key proteins involved in apoptosis and metastasis regulation, including Bax, Bcl-2, survivin, and MMP-9. Furthermore, we observed a significant improvement in oral bioavailability (2.8-fold) with the exosomal formulation and enhanced in vivo anti-cancer activity of DHA. Notably, treatment with Exo-DHA resulted in strong enhancement of tumor growth suppression and reduced melanoma cell metastasis compared to free DHA. © Controlled Release Society 2025.